PEMAHAMAN KONSEP SISWA KELAS IV MATERI PENCEMARAN LINGKUNGAN MELALUI PEMBELAJARAN RADEC - Zahra, Amelia; Sujana, Atep; Ali, Enjang Yusup (Jurnal Gentala Pendidikan Dasar, 2026)
Environmental pollution is one of the science topics that requires students to possess a strong conceptual understanding to comprehend the relationships between environmental phenomena and their impacts. However, students’ conceptual understanding remains relatively low due to teacher-centered learning practices. This study aimed to determine the effectiveness of the Read, Answer, Discuss, Explain, and Create (RADEC) learning model in improving fourth-grade students’ conceptual understanding of environmental pollution. The study employed a quasi-experimental method with a nonequivalent control group design involving 60 fourth-grade students divided into an experimental class and a control class. Data were collected through pretest and posttest instruments measuring students’ conceptual understanding. The data were analyzed using normality tests, homogeneity tests, independent sample t-tests, paired sample t-tests, and N-gain analysis. The results showed a significant difference between the experimental and control classes, with a significance value of 0.008 (< 0.05). Furthermore, the paired sample t-test yielded a significance value of 0.000 (< 0.05), indicating a significant improvement in students’ conceptual understanding after the implementation of the RADEC model. The N-gain analysis revealed an average gain score of 70.00% in the experimental class, which was higher than that of the control class (40.37%). These findings indicate that the RADEC learning model is effective in enhancing fourth-grade students’ conceptual understanding of environmental pollution.